2005
DOI: 10.1186/1475-2840-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Serum resistin is associated with C-reactive protein and LDL- cholesterol in type 2 diabetes and coronary artery disease in a Saudi population

Abstract: Aims: Resistin is an adipocyte-derived factor implicated in obesity-associated type 2 diabetes (T2DM). This study examines the association between human serum resistin, T2DM and coronary heart disease. Methods:One hundred and fourteen Saudi Arabian patients (male: female ratio 46:68; age 51.4 (mean ± SD)11.7 years; median and range: 45.59 (11.7) years and BMI: 27.1 (mean ± SD) 8.1 Kgm 2 median and range: 30.3 (6.3) were studied. Serum resistin and C-reactive protein (CRP), a marker of inflammation CRP levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Some studies reported that serum resistin was significantly associated with CRP in patients. 32 33 In this study, resistin was significantly correlated with CRP in both sexes. A previous study showed that CRP level was significantly higher in the BSS group with high serum amyloid P component (SAP) level.…”
Section: Discussionsupporting
confidence: 52%
“…Some studies reported that serum resistin was significantly associated with CRP in patients. 32 33 In this study, resistin was significantly correlated with CRP in both sexes. A previous study showed that CRP level was significantly higher in the BSS group with high serum amyloid P component (SAP) level.…”
Section: Discussionsupporting
confidence: 52%
“…In this work, the hs-CRP levels were higher in rats receiving the oxysterol diet than in rats receiving the cholesterol or standard diets. If we focus on the hs-CRP results in connection with resistin levels, also increased in rats receiving oxysterols, we can hypothesize that resistin may also play a role as a good marker of cardiovascular risk, as it has been previously demonstrated in populations with type 2 diabetes and coronary heart disease [36].…”
Section: Discussionmentioning
confidence: 88%
“… 43 Furthermore, Aldaghri et al (2005) showed that serum resistin is related to both LDL and CRP, providing a possible link between insulin resistance, hyperlipidemia and inflammation. 44 …”
Section: Specific Diabetes Syndromesmentioning
confidence: 99%